Study on customer satisfaction towards service quality in Kuwait finance house Kuala Lumpur main branch / Muhammad Nazmi Nawi - Nawi, Muhammad Nazmi (2010)
This study was designed to examine the relationship between customer satisfaction towards the service quality provided by the Kuwait Finance House Malaysia Berhad (KFHMB) Kuala Lumpur main branch and also to identify the most significant element that give the high impact to the customer satisfaction towards the service quality provided by the KFHMB Kuala Lumpur main branch. The CARTER model with six-elements (Compliance, Assurance, Reliability, Tangible, Empathy, and Responsiveness) has been applied in this research to measure the service quality provided by the KFHMB Kuala Lumpur main branch. The research has been conducted using 50 respondents which is the existing customer of KFHMB Kuala Lumpur main branch. The bivariate correlation used in this research shows that there is good positive relationship between the service quality provided with the customer satisfaction. Whereas the result from the multiple linear regression method shows that the most significant element in the CARTER model that affects the customer satisfaction is empathy element. The result from of R square value in multiple linear regression show that 80% of the variance of the dependent variable was explained by the independent variable and the remaining 20% is not explained by the existing independent variables.